2007
DOI: 10.1080/02713680601161238
|View full text |Cite
|
Sign up to set email alerts
|

Sustained Elevation of Intracellular cGMP Causes Oxidative Stress Triggering Calpain-Mediated Apoptosis in Photoreceptor Degeneration

Abstract: Sustained elevation in cGMP and a concomitant increase in intracellular Ca(2+) levels in the rd1 photoreceptors are followed by a rapid loss of photoreceptors. In a murine-derived photoreceptor cell line, 661W, treated with the phosphodiesterase inhibitor IBMX or the cyclic GMP-gated channel agonist 8-bromo-cGMP, it was previously found that the induced cell death was mediated by calpain and caspase-3. Because oxidative stress is a common product of ionic imbalance or elevated Ca(2+), we tested the role of oxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
46
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(49 citation statements)
references
References 34 publications
3
46
0
Order By: Relevance
“…PKG I expression was not determined in the studies demonstrating a lack of cGMP-mediated protection (8,54,60). A recent study in retinal cells (52) found that cGMP triggered apoptosis through the direct activation of a cyclic nucleotide-gated cation channel thus demonstrating a PKG I -independent, proapoptotic cGMP effect. In contrast, our results in PKG I Ϫ/Ϫ MLMVECs (Fig.…”
Section: Discussionmentioning
confidence: 95%
“…PKG I expression was not determined in the studies demonstrating a lack of cGMP-mediated protection (8,54,60). A recent study in retinal cells (52) found that cGMP triggered apoptosis through the direct activation of a cyclic nucleotide-gated cation channel thus demonstrating a PKG I -independent, proapoptotic cGMP effect. In contrast, our results in PKG I Ϫ/Ϫ MLMVECs (Fig.…”
Section: Discussionmentioning
confidence: 95%
“…ROS can lead to calpain activation (47,48), although this pathway has not been implicated previously in inflammation. We used ALLN, a calpain inhibitor, to test whether calpain is in- fl/fl LysM-Cre − BMM and Atg5 fl/fl LysM-Cre + BMM knocked down with siRNA for Calpain S1.…”
Section: (B-d) Intracellular Levels Of Il-17a (B and C) And Ifn-γ (D mentioning
confidence: 97%
“…The fundamental outcome from our studies is that even a retina that is metabolically overloaded can maintain its function until a threshold level for cell death is reached. When we applied sildenafil to the P23H-3 rat model, we were able to modify retinal LDH activity, which suggests a downregulation of aerobic metabolism and/or accelerated photoreceptor death, reminiscent of that noted in other retinal dystrophy models (RCS and rd/rd retina) (3,9,87). Inhibition of phosphodiesterase affects the already compromised cellular environment of the P23H-3 retina (high oxygen tension and high ATP levels) but not that of the normal SD retina.…”
Section: C771mentioning
confidence: 62%